Weathering of aromatic engineering thermoplastics: Comparison of outdoor and xenon arc exposures. (February 2019) - Kuvshinnikova, Olga; Boven, Gert; Pickett, James E.
Abstract: A series of 31 aromatic engineering thermoplastic formulations was exposed at outdoor sites in Florida, Arizona, and the Kingdom of Saudi Arabia (KSA) for 24 months as well as under modified ISO 4892-2 xenon arc accelerated weathering conditions. The series included black, white, and transparent formulations. Measured properties were color, gloss, haze, transmission, tensile strength and elongation, Charpy impact, and erosion. There was surprisingly little difference in weathering among the outdoor sites except for the effects of blowing sand and slower erosion at the KSA site. Xenon arc accelerated weathering run at high irradiance and using state of the art filters provided very good predictions of color shifts, transmission, Charpy impact mode (break/no break), and tensile elongation at break. Prediction of gloss loss was only fair, especially for black samples, and haze was poorly predicted on the transparent samples. This suggests the need for better simulating the effects of rain and wind in accelerated weathering cabinets. Tensile strength and Charpy impact strength generally exhibited little change and were not useful properties to differentiate material performance. Highlights: A series of engineering thermoplastics was subjected to xenon arc accelerated weathering and outdoors at three sites. Accelerated conditions were ISO 4892-2 modified using Atlas Right Light™ filters and higher irradiance. Accelerated conditions gave good predictions of color shifts, erosion rates, elongation at break, and Charpy impact mode. The accelerated conditions gave poorer predictions of gloss loss and haze. The results suggest the need for better reproduction of the effects of rain and wind on weathered surfaces.